Foucault, historicism and political philosophy - Allsobrook, Christopher John (Rhodes University, Faculty of Humanities, Department of Philosophy, 2006)
This thesis defends an ontological and epistemological account of Michel Foucault's post-structuralist philosophy, to argue that political philosophy needs to take into account the historical and political contingency of subjectivity and discourse. I show that by addressing the historical and political contingency of knowledge, Foucault's work overcomes the flaw of foundational epistemology in political philosophy, which treats true discourse as universal and disinterested. In doing so I hope to have to refuted the mainly positivistic and humanist schools of thought that lay claim to universal and foundationalist notions, by demonstrating the extent to which their misgivings about Foucault's work are informed by and founded upon an unjustified a-historicism. The thesis is composed of three chapters, the first of which deals with an ontology of the subject, the second, with an ontology of social relations, and the last with epistemology. In each chapter I use dialectical analysis to reveal how interests necessarily mediate subjectivity, social relations, and knowledge. The first two chapters defend Foucault's conception of power, by way of an analysis of the relations between Foucault's work and Sartre's existential phenomenology. I show how both Foucault and Sartre successfully address the problem of historicism for political philosophy with their respective conceptions of human freedom. The final chapter defends Foucault's conception of the relations between power and discourse, to show how it overcomes the a-historicism of universal, foundational epistemology. These three chapters demonstrate the importance of accounting for historicism in political philosophy. Claims to universal interest, because knowledge is conditioned by conflicts of interest, often mask political domination. It is important, then, to remember, in political philosophy, that knowledge is evaluative and interested, reflecting historically and politically mediated evaluations. One should be suspicious of ' natural facts' , used to justify actions or beliefs, thereby masking the choices that inform them. I have used the work of Michel Foucault to motivate this claim.
Keywords: Foucault, Michel, 1926-1984; Sartre, Jean Paul, 1905-1980; Political science -- Philosophy; Power (Philosophy); Existential phenomenology; Knowledge, Theory of; History -- Philosophy; Historicism